The association between contraceptive use and desired number of children among sexually active men in Zambia - Bwalya Bupe Bwalya; Mwewa E. Kasonde; James Nilesh Mulenga; Chabila Christopher Mapoma; Nayunda Wamunyima; Billy Siamianze; Obinna Onukogu (BMC, 2023)
Abstract Background Contraceptive methods have been used to space births, but also to limit a couple's desired number of children. Efforts of family planning programmes have mainly concentrated on females, even though males tend to have large say on the desired number of children a couple should have. In our study, we sought to determine linkages between contraceptive use and desired number of children, as well as associated demographic and socio-economic characteristics, among sexually active males in Zambia. Methods The main outcome variable of interest was desired number of children as measured by ideal number of children which is a count variable. Data for this paper was the male dataset from the 2018 Zambia Demographic and Health Survey, a cross-sectional national survey. Binary logistic regression was performed to determine odds ratios of contraceptive use by selected characteristics of sexually active males. Multivariate Poisson Regression Model was used to establish factors associated with desired number of children. Results Age of men (20-29, 30-39 and 40-49 years), residence in rural areas, wealth quintile, Protestant or Muslim religious affiliation, media exposure, and having discussed family planning with a health worker in the last few months prior to the survey were associated with contraceptive use. Sexually active males who reported using any contraception method reported 3% less desired number of children compared to those who were not using any method. Older males (age group 30-49 years), resident in rural areas, with primary education, married, employed, Protestant religion, and those labelling women who use contraceptives "as promiscuous" had more desired number of children. Conclusions There were minimal differences in the desired number of children among males who reported using and not using any contraceptive method. Strategies aimed at encouraging contraception use should cover all categories of males to achieve universal involvement of men in family planning in Zambia. Future research may consider combining both qualitative and quantitative methods to look holistically at the demographic, socio-economic and cultural factors associated with non-contraception use and desired number of children among sexually active men in Zambia.